Interdisciplinary Comparison of the Index of Social Well-being of the Russian Population with Economic Indicators (Based on the Example of Republic of Tatarstan) - Ermolaeva, Polina O.; Demkina, Elena P.; Zajnullina, Muluasha R. (Journal of History Culture and Art Research, 2018)
Based on the monitoring of population-based surveys of representative samples of data and economic analysis, the article presents the results of a multidisciplinary comparison of socio-economic indicators with the index of social well-being of Russians based on the example of the Republic of Tatarstan. The results showed that in spite of the fact that current economic situation evaluation index in the Republic of Tatarstan for the period from November 2012 to November 2013 increased by more than a third (34.3 percent), the real economic indicators have recorded only a slight increase in selected industries and regional economic development index has decreased by 2.77 percent. Overall, according to perception surveys taken in the period from November 2012 to November 2013 concerning changes in economic situation and in personal welfare, people of Tatarstan are more optimistic than the actual economic changes. The changes in the economy are evaluated more positively than changes in personal welfare. Nevertheless, objective indicators suggest otherwise: economic growth is observed only in some sectors of the economy with negative growth in the composite index of economic development of the region (-2,77%), while growth of incomes of the population amounted to an average of +10.83%. Such dissonance between the subjective and objective assessments can be linked to many interdependent factors: first, public opinion and the subjective perception of the economic situation of the population in particular, has a catch-up character – it usually lags behind the real economic situation; secondly, the positive perception of the economic situation can be fabricated by the media in the interests of the ruling elite and private corporations; thirdly, the positive perception of micro-situation in the economy can be imposed by a high assessment of the current personal situation (growth of incomes and well-being of the population).